2016
DOI: 10.1177/0218492316644355
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of total anomalous systemic venous connection

Abstract: A 9-year-old girl who presented with dyspnea on exertion was diagnosed with total anomalous systemic venous connection to the left atrium (both venae cavae), no left superior vena cava, and a moderate-sized atrial septal defect with severe pulmonary arterial hypertension and ectopic atrial rhythm. She underwent septation of the common atrium using autologous pericardium, thereby rerouting the superior vena cava, inferior vena cava, and coronary sinus to the right atrium. Her postoperative course was uneventful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Total abnormal systemic venous return requires a left-to-right shunt through an atrial septal defect, a ventricular septal defect, or a patent arterial duct in order to ensure pulmonary circulation. A large atrial septal defect was present in all patients of studies previously published [3][4][5][6]8 except for two of them. A 7-year-old girl had a large perimembranous ventricular septal defect, 7 and a 2-year-old boy had only a small atrial septal defect.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Total abnormal systemic venous return requires a left-to-right shunt through an atrial septal defect, a ventricular septal defect, or a patent arterial duct in order to ensure pulmonary circulation. A large atrial septal defect was present in all patients of studies previously published [3][4][5][6]8 except for two of them. A 7-year-old girl had a large perimembranous ventricular septal defect, 7 and a 2-year-old boy had only a small atrial septal defect.…”
Section: Discussionmentioning
confidence: 83%
“…Most cases of total anomalous systemic venous connection to the left atrium reported in the literature were associated with left isomerism. [5][6][7][8] On surgical inspection of the appendage of the right-sided atrium, we found that it exhibited the anatomical characteristics of a left-atrial appendagenamely, a long narrow chamber with a smooth-looking wall, possibly indicating heterotaxy syndrome with left-atrial isomerism. The chest X-ray, however, did not show bilateral symmetric left bronchi with widened carina as typically observed in left bronchial isomerism.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[ 2 3 4 5 6 7 8 9 ] On the other hand, the presence of a large shunt allows good oxygenation, together with the growth of RV, thus permitting complete surgical repair. [ 9 10 11 12 13 14 15 16 17 18 19 ] The presence of cyanosis despite left-to-right shunt across an ASD, in the setting of a hypoplastic RV in hearts with concordant atrioventricular and ventriculoarterial connections, is almost diagnostic of totally anomalous systemic venous connection (TASVC). Unfortunately, even in the current era of modern echocardiography, despite many clues, the diagnosis is often delayed.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, even in the current era of modern echocardiography, despite many clues, the diagnosis is often delayed. [ 5 8 11 12 14 15 20 ] Not uncommonly, the diagnosis is missed completely,[ 10 ] and the arrangement is misinterpreted as functionally single ventricle. It is also not uncommon to find that anomalous connection of only one caval vein, generally the superior caval vein (SCV), is correctly identified mainly because saline contrast echocardiography is generally performed only from the upper limb.…”
Section: Introductionmentioning
confidence: 99%